2020
DOI: 10.1016/j.buildenv.2020.106859
|View full text |Cite
|
Sign up to set email alerts
|

Short-range airborne route dominates exposure of respiratory infection during close contact

Abstract: A susceptible person experiences the highest exposure risk of respiratory infection when he or she is in close proximity with an infected person. The large droplet route has been commonly believed to be dominant for most respiratory infections since the early 20 th century, and the associated droplet precaution is widely known and practiced in hospitals and in the community. The mechanism of exposure to droplets expired at close contact, however, remains surprisingly unexplored. In this study, the exposure to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
215
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 294 publications
(252 citation statements)
references
References 55 publications
(51 reference statements)
11
215
0
2
Order By: Relevance
“…This yields ∼5000 undetected infectious individuals on a given day, or a 0.6% base rate and corresponding risk threshold. Several studies have found the secondary attack rate to be on the order of 1/10 -1/100 [15,16,17], so this risk threshold aligns well with standard guidelines for the minimum contact considered close for tracing purposes. We note that 14 day quarantine is more than is needed to put the conditional probability of infectiousness, given lack of symptoms, of a non-household close contact below the base rate [7].…”
Section: Examples Of Applicationsupporting
confidence: 74%
“…This yields ∼5000 undetected infectious individuals on a given day, or a 0.6% base rate and corresponding risk threshold. Several studies have found the secondary attack rate to be on the order of 1/10 -1/100 [15,16,17], so this risk threshold aligns well with standard guidelines for the minimum contact considered close for tracing purposes. We note that 14 day quarantine is more than is needed to put the conditional probability of infectiousness, given lack of symptoms, of a non-household close contact below the base rate [7].…”
Section: Examples Of Applicationsupporting
confidence: 74%
“…The human-to-human transmission routes of COVID-19 are the inhalation of aerosols or droplets (Jayaweera et al 2020 ) and contact with fomites (WHO 2020 ). Virus-laden droplets and aerosols can travel under the effects of wind speed by distances from less than 2 m with normal exhalation (Chen et al 2020 ; Ong et al 2020 ) and more than 6 m with cough and sneeze (Jayaweera et al 2020 ). However, the lifetime of COVID-19 is 1–5 and 1–18 h in aerosols and on the furniture surfaces (made of copper, cardboard, stainless steel, or plastic), respectively (van Doremalen et al 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…With the current coronavirus disease (COVID-19) pandemic caused by SARS-CoV-2, all supplies of surgical and respiratory masks are severely depleted, in part due to the decreased production and disruption of the supply chain secondary to the effects of the pandemic on industrial workers, particularly in China, where this disease originated. Simultaneously, there is increased use of facemasks in response to a novel, deadly respiratory virus primarily transmitted via short-range, airborne respiratory droplets (1,17). This increased use of facemasks is warranted based on existing English language literature regarding other viral respiratory infections with pandemic potential and similar transmission patterns, including SARS, MERS, and influenza (18)(19)(20).…”
Section: Sars-cov-2 and The Need For Facemasksmentioning
confidence: 99%